Underrepresentation of women in cardiovascular disease clinical Trials—What’s in a Name? - A.E. Spiering; A.M.L.N. van Ommen; J.E. Roeters van Lennep; Y. Appelman; K. Reue; N.C. Onland-Moret; H.M. den Ruijter (International Journal of Cardiology: Heart & Vasculature)
Background: Cardiovascular disease is the leading cause of death in women worldwide. Yet, women are often underrepresented in cardiovascular clinical trials. Trial characteristics may influence the participation of women. For instance, trials are often entitled with an acronym, which might be perceived as gendered. We aimed to investigate if the perceived gender of the acronym and other trial characteristics affect the representation of female patients in cardiovascular trials. Methods: We searched ClinicalTrials.gov for randomized controlled trials in cardiovascular disease named with an acronym. Cardiovascular patients (n = 148) scored the perceived gender of the acronym of 148 identified trials. Prevalence ratios (PR) were calculated with Poisson regression to link trial characteristics to representation of female patients in the trials. Results: In 62 % of trials, female patients were underrepresented relative to the disease population. There was no improvement over time in proportion of trials with adequate representation. A third of acronyms was classified as gendered. The perceived gender did not affect representation of female patients (PR 1.01; 95% CI 0.95 – 1.08; P = 0.68). A woman as first and/or last author (PR 1.22; 95% CI 1.07 – 1.38; P = 0.002) and recruitment in an outpatient setting (PR 1.15; 95% CI 1.02 – 1.29; P = 0.01) were associated with a higher prevalence of adequate representation of female patients. Conclusions: Representation of female patients in cardiovascular trials does not depend on the perceived gender of the trial acronym but is improved in trials under female leadership in out-patient settings. Our findings may direct efforts towards increasing representation of female patients in cardiovascular trials.